Comparison of Deep Regional Integration in the Melitz, Krugman and Armington Models : The Case of The Philippines in RCEP - Balistreri, Edward J.; Tarr, David G. (World Bank, Washington, DC, 2018)
This paper estimates the impacts on The Philippines of deep integration in a modern mega-preferential trade agreement, the Regional Comprehensive Economic Partnership. The paper assesses how the results differ with three versions of market structure: (i) perfect competition, Armington style; (ii) monopolistic competition Krugman style; and heterogeneous firms, Melitz style. The paper develops a new numerical model of foreign direct investment with heterogeneous firms where firms produce in the host country and demand corresponds to the “proximity burden,” and is the first to apply a heterogeneous-firms model of foreign direct investment to preferential trade analysis. It also develops an extension of the Krugman model that allows small countries to impact the number of varieties. Both of these model extensions, as well as market structure, are crucial to the results. The trade and foreign direct investment responses are held constant across the three market structures. Lowering trade costs is examined from: (i) the reducing non-tariff barriers in goods; (ii) lowering barriers against foreign services providers, from foreign direct investment and cross-border; and (ii) facilitating trade. The results show that in all three market structures, there are substantial gains from deep integration, but virtually no gains from preferential tariff reduction. Both Krugman and Melitz style models produce significantly larger welfare gains than the Armington structure, especially in the impacts of foreign direct investment or with wider spillover effects on non- Regional Comprehensive Economic Partnership regions. The relationship between the welfare gains in the Krugman versus Melitz models is complex.